2016
DOI: 10.1007/s12687-016-0277-1
|View full text |Cite
|
Sign up to set email alerts
|

Population-level diversity in the association of genetic polymorphisms of one-carbon metabolism with breast cancer risk

Abstract: Aberrations in one-carbon metabolism were reported to increase breast cancer risk by influencing the DNA synthesis and methylation of DNA and catecholamines. However, the results of these association studies remain inconclusive. We have explored the contribution of eight genetic polymorphisms in modulating the susceptibility to breast cancer by performing a meta-analysis of worldwide studies. In total, 62 case-control studies representing 17 different populations involving 18,117 breast cancer cases and 23,573… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Fig. 2 A network analysis of the associated genes using GeneMANIA database worldwide populations [35] including African American women [36]. Our data revealed the variant rs1051266 to be significantly associated with BC risk in the population under study.…”
Section: Network Analysismentioning
confidence: 70%
See 1 more Smart Citation
“…Fig. 2 A network analysis of the associated genes using GeneMANIA database worldwide populations [35] including African American women [36]. Our data revealed the variant rs1051266 to be significantly associated with BC risk in the population under study.…”
Section: Network Analysismentioning
confidence: 70%
“…SLC19A1 or Solute Carrier family member protein is a gene implicated in placental carcinomas and pediatrics osteosarcomas. Studies have shown the SLC19A1 gene variants to be associate with BC risk in worldwide populations [ 35 ] including African American women [ 36 ]. Our data revealed the variant rs1051266 to be significantly associated with BC risk in the population under study.…”
Section: Discussionmentioning
confidence: 99%
“…The 5,10-methylene tetra hydrofolate (THF) is the common substrate for two key enzymes of TYMS and methylenetetrahydrofolate reductase (MTHFR). These enzymes catalyze the conversion of deoxyuridine monophosphate (dUMP) to deoxythymidine monophosphate (dTMP) and flavin adenine dinucleotide (FAD)-dependent reduction of 5,10-methylene THF to 5-methyl THF, respectively ( 9 ). The dTMP is necessary for DNA synthesis and repair.…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted, rs1048943 of CYP1A1 showed a signi cant association with lung cancer 31 , while the same variant showed no signi cant association with lung cancer in a different study from the Indian subcontinent 36 . The differences in genetic association across the geographical regions of the Indian subcontinent, comprised of distinct population groups, might be attributed to gene-gene and gene-environment interactions, which could act as potential modulators of lung cancer risk 37 . The contradictory outcomes of the variant between different studies could be due to small sample sizes, clinical heterogeneity between the populations, and racial/ethnic differences 38 within the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%